ANALISIS STRATEGI PEMASARAN JASA PARIWISATA PADA PT RADEN GEMPITA WISATA TOUR & TRAVEL PALEMBANG - Nina Fitriana; Noviarni . (JURNAL KOMPETITIF, 2015)
AbstractÃ‚Â A thriving business world in Indonesia increasingly heavy in the position as the industry and employers in dealing with other industry competitors. Strategies and appropriate consideration should be owned businesses in the face of competition .PTÃ‚Â  RadenÃ‚Â  Gempita Travel and Tour l is one of the travel agencies in Palembang in marketing their products PT Raden Gempita Tour and Travel using the marketing mix strategy which consists of product, price, promotion, place, people, procces, physical evidence. The purpose of this study was to identify and analyze the marketing strategy services using the marketing mix variables were performed by the company to increase sales of tourism services. ResultÃ‚Â  of research shows that; The first, from the aspect of promotion lowest level according to 51.84% of respondents Raden Gempita Tour and Travel is still not optimal in promoting the product, this is due to the ineffectiveness of the distribution of brochures, advertisements either by newspaper, television, the Internet or in the form of billboards , Both companies can use the model of growth through horizontal integration strategy for the control of competitors. Keywords: Marketing Strategy, Tourism ServicesÃ‚Â